Tongue cancer in non-smoking and non-alcoholic mother and daughter - de Melo Cardoso, Diovana [UNESP]; Conrado Neto, Sebastião [UNESP]; Urbano Collado, Francisco [UNESP]; Furuse, Cristiane [UNESP]; Callestini, Renata [UNESP]; Bonetti Valente, Vitor [UNESP]; Ricardo Biasoli, Éder [UNESP]; Issamu Miyahara, Glauco [UNESP]; Galera Bernabé, Daniel [UNESP] (Elsevier, 2024)
Tongue cancer is more prevalent in male smokers and alcoholics. Although an increased incidence of tongue cancer has been noted in non-smoking and non-alcoholic women, reports of its occurrence in mother and daughter are extremely rare. Here, we report a case of a non-smoking and non-alcoholic mother and her daughter diagnosed and treated surgically for tongue squamous cell carcinoma (SCC). The daughter is still being monitored and the mother died from complications from COVID-19 after 6 years of treatment. This report shows that OSCC should be considered in the differential diagnosis of oral ulcerated lesions in non-smoking and non-alcoholic women, especially if there is a family history of first-degree oral cancer.
Keywords: Cancer; Carcinoma cell squamous; Daughter; Familial risk; Family; Hereditary; Mother; Oral cancer; Oral cavity